MAID ready for primetime?: A survey of SGO members regarding medical aid in dying (MAID) - Alaina J. Brown; Nefertiti duPont; Ronald D. Alvarez; Monique A. Spillman; Lisa Landrum; Carolyn Lefkowits (Elsevier, 2021)
Objectives: To assess SGO members' knowledge, attitudes, and practice patterns regarding Medical Aid In Dying (MAID). Methods: SGO members were surveyed via online survey. The survey included questions regarding demographics, knowledge, attitudes, and practice patterns relating to MAID. Descriptive statistics were calculated. Associations between sociodemographic factors and attitudes related to MAID were analyzed utilizing logistic regression. Results: Of 1,337 invited members, 225 (17%) responded. Median age was 46. Most were female (58%), white (81%), and in academic practice (64%). Over 50% had heard the term MAID and have had a patient ask about it. Few (20%) reported living in a state where MAID is legal and 61% of these respondents provided MAID. Sixty percent lived in a state that had not legalized MAID and 18% did not know if MAID was legal in their state. 36% of respondents living in a state where MAID was illegal/unknown legality indicated they would provide MAID if it were legal in their state, 30% would not, and 34% were uncertain. The majority (69%) of respondents believed MAID should be legal. Female respondents were more likely to support legalization of MAID (OR 2.44, p=<0.05). Respondents practicing in the southern U.S. were less likely to support legalization of MAID (OR 0.42, p=<0.05). Over 75% of respondents stated an SGO position statement on MAID would be helpful. Conclusions: MAID is a highly relevant topic for gynecologic oncologists. Gaps in MAID-related knowledge exist among SGO members and there is a desire for additional education and guidance regarding MAID.